Practice Guidelines for Obstetrics and Gynecology, 2nd Edition - Morgan, Geri, Hamilton, Carole (Lippincott Williams & Wilkins, 2003)
Guidelines for Well Woman Care Common Discomforts of Pregnancy Abuse, Domestic Violence, and Sexual Coercion or Assault Management of Common Problems and Procedures in Pregnant and Nonpregnant Women Management of Common Problems and Procedures Specific to Pregnancy Complementary Therapies Drug Index Topical Agents